Mechanisms of Heme Utilization by Francisella tularensis - Lindgren, Helena (Public Library of Science, 2015)

(untitled) (PLoS One)
Francisella tularensis is a highly virulent facultative intracellular pathogen causing the severe disease tularemia in mammals. As for other bacteria, iron is essential for its growth but very few mechanisms for iron acquisition have been identified. Here, we analyzed if and how F. tularensis can utilize heme, a major source of iron in vivo. This is by no means obvious since the bacterium lacks components of traditional heme-uptake systems. We show that SCHU S4, the prototypic strain of subspecies tularensis, grew in vitro with heme as the sole iron source. By screening a SCHU S4 transposon insertion library, 16 genes were identified as important to efficiently utilize heme, two of which were required to avoid heme toxicity. None of the identified genes appeared to encode components of a potential heme-uptake apparatus. Analysis of SCHU S4 deletion mutants revealed that each of the components FeoB, the siderophore system, and FupA, contributed to the heme-dependent growth. In the case of the former two systems, iron acquisition was impaired, whereas the absence of FupA did not affect iron uptake but led to abnormally high binding of iron to macromolecules. Overall, the present study demonstrates that heme supports growth of F. tularensis and that the requirements for the utilization are highly complex and to some extent novel.